The State and agricultural labour: Zanzibar after slavery - Cooper, Frederick (My University, 1981)
The march of capitalism into Africa is often made to appear inexorable. Indeed, some scholars have defined the possibility of a failure, a missed possibility of domination, out of existence: the survival of pre-capitalist modes of production are simply a way by which the costs of labor or cash crops are subsidized by subsistence cultivation. But how is one to tell whether the cultivator's access to the soil represents a dangerous automony, a tenacious resistance to becoming subject to industrial work rhythms and control over all aspects of a working life, or else constitutes a perfectly functional part of a superexploitative system?The conditions of rural and urban workers in South Africa is likely to suggest itself in answer to that question. But the best of research in South African labor history has focused on the specific processes by which labor was controlled and has not neglected the persistence of resistance — in individual and daily behaviour in farms and factories as much as in collective action.2 A look beyond South Africa emphasizes how elusive similar objectives could be, and how essential it is to ask just what kind of transformations capital and the state sought, how they tried to effect them, and what they were unable to do.3 Much of the literature on the "articulation" of modes of production stresses structural juxtapositions, not processes. And that gets away from the most basic if most difficult aspects of Marx's treatment of capitalism, that it was based on two quite particular and quite well masked forms of coercion: primitive accumulation— the permanent alienation of workers from the means of productionand the labor process itself- the daily struggle to make workers work. Primitive accumulation is not the mere amassing of resources, nor is it legal title to land: it is the effective exclusion of acess to the means of production of an entire class. And to say that means to ask how they were kept away. The labor process itself entails distinct mechanisms—from supervision on the shop floor to the educational system—to control the pace and intensity of labor, which in turn foster distinct patterns of resistance. Our task is not to arrive at a rigid and pristine definition of capitalism, but to look at accumulation and the labor process as the specific and complex phenomena they are. They embody the action of people and institutions, and the consequences of such actions not being complete need to be taken seriously. This study of Zanzibar looks at an attempt that penetrated to the heart of the labor process, an effort to make slave labor into wage labor. It involved non-white landowners and non-white workers in a British colony, but the division between landowners and workers was no less fundamental for the racial complexity of Zanzibar. British officials were clear that they wanted to make slaves into an agricultural proletariat, but they ended up with a complex system of labor migration, shaped as much by the ex-slaves as by the state or the ex-slaveowners. I have discussed the evidence and details of this process at length elsewhere; my aim here to to discuss some basic issues that it raises in terms that might suggest comparative perspectives.
African Studies Seminar series. Paper presented June, 1981
Keywords: Zanibar. History